School sports in full-time education: the National Education Plan 2014-2024 - Fernando Henrique Silva Carneiro; Fernando Mascarenhas; Wagner Barbosa Matias (Universidade Estadual do Oeste do Paraná, 2017)
The study reflects on the goal 6 of the National Education Plan (PNE - Law n 13.005/2014) and its strategies regarding sports practice. The quantitative and qualitative research was based on documentary analysis. It was realized that it was an advance to have a specific goal for full-time education in the Plan and that it would be easier for the country to achieve the desired percentage of full-time schools (50%) than to have the percentage of students expected ( 25%). As for sport, it is undoubtedly one of the main activities offered, although there is a debate in PNE that contradicts cognitive activities with recreational, sports and cultural activities. In addition, it was identified that the lack of adequate infrastructure in schools is one of the main limits for the development of classes, and symptomatic of this is the lack of sports courts.